Nonuniform reinjection probability density function in type V intermittency - Elaskar, Sergio Amado (2018)
In this paper, type V intermittency is studied using the M function methodology developed in the last years. This methodology is applied on two different maps to evaluate the reinjection probability density function (RPD), the probability density of laminar lengths and the characteristic relation. We have found that the RPD can be written as an exponential function, where the uniform reinjection is only a singular case. Also, the probability density of laminar lengths can be a nondifferentiable function when the local map has a nondifferentiable point inside the laminar interval. On the other hand, the characteristic relation is not unique, and it depends on the local map. Therefore, the behavior of the reinjection processes and the statistical properties for type V intermittency is wider than the previous studies have described. Finally, it is noted that the M function methodology is a suitable tool to analyze type V intermittency.